PENGARUH PENAMBAHAN EKSTRAK ROSEMARY TERHADAP KUALITAS KIMIA SUSU KAMBING PASTEURISASI: THE EFFECT OF ADDING ROSEMARY LEAF EXTRACT ON THE CHEMICAL QUALITY OF PASTEURIZED GOAT MILK - Maulana, Rafli Adrian Maulana; Abdurrahman, Zakaria Husein; Prasetyo, Aris Budi (Universitas Boyolali, 2025)
This study aims to determine the effect of adding rosemary leaf extract on the chemical quality of pasteurized goat milk. The materials used in this study were Etawa crossbreed goat milk, rosemary, water, and sugar. The experimental design used was a completely randomized design with four treatments and five replications. The treatments given were P0 = Pasteurized Milk without the addition of rosemary plants (as a control), P1 = Pasteurized Milk with the addition of 1.5 g of rosemary plants as much as 50 ml, P2 = Pasteurized Milk with the addition of 3 g of rosemary plants as much as 50 ml, and P3 Pasteurized Milk with the addition of 5 g of rosemary plants as much as 50 ml. The research data were analyzed using analysis of variance. The results showed that the addition of rosemary leaf extract to pasteurized goat milk affected the chemical quality carried out at Boyolali University. The Lacktoscan test showed a very significant effect (P <0.01) on lactose, protein, fat, and total solid levels. The conclusion of this study is that the addition of rosemary leaf extract affects the chemical quality of pasteurized goat milk in terms of lactose, protein, fat, and total solids but does not affect density. In general, this concentration has an effect, but it is necessary to identify the optimal dose so as not to reduce nutritional quality